Reproductive Biology of Anabas testudineus living in the palm tree plantation canal , Tapung Kiri River , Bencah Kelubi Village, Riau Province - Dwi Sumba Vicaya; Deni Efizon; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
Climbing perch (Anabas testudineus) is the one of freshwater fishes living inRiau. Information on the biological aspect of this fish, however, is limited. Astudy aims to understand the reproductive biological aspect of this fish has beenconducted from January-March 2014. The fish was sampled once/ month for athree months period. They were 153 fishes, 68 males and 85 females, 49-145mm SL and 4-126 gram BW. Sex ratio of females and males was 1:1,25. In eachsampling, male and female fishes in 1st , 2nd , 3rd and 4th maturity stages werecaptured, and only female in 5th maturity level was captured. The gonado somaticindex (GSI) is around 0.0088%-5.8567%. Fecundity is around 4.116-13.998eggs/fish, with mature egg diameter ranged from 0.62-0.69 mm. Microscopicstudy of the ovarian structure showing that the ovary of mature femalesdominated by mature eggs and there were few amount of non vitellogenic andearly vitellogenic eggs. The atretic eggs were found in the ovary of the 5thmaturity level fish only. This structure indicates that the fish may be a totalspawner. The testes of males showing mature sperms throughout the study period,indicates this fish may be able to spawn throughout the year.Keywords: Anabas testudineus, Reproduction, sex ratio, GSI, fecundity, sexreversal